2009
DOI: 10.1029/2008jc005128
|View full text |Cite
|
Sign up to set email alerts
|

Surface distributions of carbon chemistry parameters in the East China Sea in summer 2007

Abstract: [1] Comprehensive carbon chemistry data including total alkalinity (TA), dissolved inorganic carbon (DIC), pH, fugacity of CO 2 , and other pertinent data (i.e., temperature, salinity, and levels of nitrate and chlorophyll a) were measured in surface waters of the East China Sea (ECS) shelf in July 2007. The results show that spatial variations in these parameters closely correspond to the distributions of various water types. The Changjiang Diluted Water (CDW) and Yellow Sea Water (YSW) areas are the two majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 62 publications
(119 reference statements)
10
74
2
1
Order By: Relevance
“…7c), lending support to the hypothesis that biologically induced DIC drawdown may be the driving force that accounts for the observed high a in the CDW. In fact, this result agrees well with previous findings that due to the favorable conditions (i.e., high availability of light and nutrients and warm temperature), the CDW area generally features very high Chl a concentrations Hung et al, 2009) and acts as a strong sink of atmospheric CO 2 in late spring and summer (Zhai and Dai, 2009;Chou et al, 2009a).…”
Section: The Role Of Freshwater Runoff On Variation In the Coastal Zonesupporting
confidence: 82%
See 2 more Smart Citations
“…7c), lending support to the hypothesis that biologically induced DIC drawdown may be the driving force that accounts for the observed high a in the CDW. In fact, this result agrees well with previous findings that due to the favorable conditions (i.e., high availability of light and nutrients and warm temperature), the CDW area generally features very high Chl a concentrations Hung et al, 2009) and acts as a strong sink of atmospheric CO 2 in late spring and summer (Zhai and Dai, 2009;Chou et al, 2009a).…”
Section: The Role Of Freshwater Runoff On Variation In the Coastal Zonesupporting
confidence: 82%
“…Previous studies have shown that the ECS shelf acts as an important sink of atmospheric CO 2 all year round (Tsunogai et al, 1999;Peng et al, 1999;Wang et al, 2000;Shim et al, 2007;Zhai and Dai, 2009;Chou et al, 2009a and. Consequently, in surface water would be continuously decreasing in response to anthropogenic CO 2 absorption.…”
Section: Aragonite Saturation States Of Surface Waters In 2100mentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations of pCO 2 were also found to be low in the Amazon River plume (Fig. 7.6), in great contrast with those found in river plumes at subtropical and temperate latitudes, where seasonal oscillations from CO 2 over-saturation (typically in winter or fall) to under-saturation (typically in spring or summer) are observed (Borges and Frankignoulle 2002;Lohrenz and Cai 2006;Chou et al 2009a;Chou et al 2009b;Guo et al 2009;Zhai and Dai 2009;Vandemark et al 2011;Bozec et al 2012). Another great contrast between the Amazon plume and some of the other large river plumes is in the DIC (or TAlk) to salinity relationship, which does not show a substantial removal in the Amazon plume (Fig.…”
Section: Co 2 In the Amazon River Plumementioning
confidence: 82%
“…Time and again, the East China Sea (ECS) has been found to be a sink of CO 2 (Chen and Wang 1999;Tsunogai et al 1999;Chou et al 2009a;Zhai and Dai 2009;Tseng et al 2011). This is in part because the Changjiang River not only exports a significant amount of nutrients to the ECS but also a large quantity of freshwater, which also helps to induce an estuarine type flow.…”
Section: Co 2 In the Changjiang River Plumementioning
confidence: 99%